The history and current state of flax (Linum usitatissimum L.) cultivation and use in Japan - Nakui, Shinya (Acta agriculturae Slovenica, 2024)
Flax (Linum usitatissimum L.) is an ancient crop that has been cultivated for thousands of years for its fiber as well as for its oil rich seeds. The crop was introduced into Japan in the end of the 17th century, but its popularity did not begin to increase until the 1890s. The production of domestic fiber flax exceeded 45,000 metric tons in the late 1910s, and Japan had a well-developed linen industry for flax processing. In the 1960s, the mass production of synthetic fibers led to the collapse of Japanese linen industry, and consequently fiber flax culture in the country disappeared. In Japan, flaxseed oil with rapid drying property was once exclusively used for manufacturing a variety of industrial products such as paints, varnishes, linoleum, and printer’s ink. Recently, this vegetable oil has gradually attracted the attention of Japanese consumers because of its health benefits mainly attributed to its high content of alpha-linolenic acid (omega-3 fatty acid). Over the past decade, the consumption of edible flaxseed oil has been increasing rapidly, but domestic oil-seed flax production remains small. In this review, we describe the history of fiber flax cultivation in Japan. The current state, problems, and perspectives of oilseed flax culture and use in the country are also presented.
Keywords: alfa linolenska kislina; alpha-linolenic acid; cultivar development; cultivation history; cultural practices; fiber flax; genetske osnove; germplasm; lan za olje; lan za vlakna; načini gojenja; oilseed flax; omega-3 fatty acid; omega-3-maščobne kisline; razvoj sort; zgodovina gojenja